Dry negative electrode, method for preparing the same, and battery
By increasing the fibrillation degree of the binder and optimizing the material ratio, a stable fiber network structure is formed, which solves the contradiction between battery energy density and structural stability in dry-process anodes, and achieves high energy density and good cycle stability of the battery.
Patent Information
- Application Number
- CN202510991041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-07-18
AI Technical Summary
While improving battery energy density, existing dry-process anodes struggle to maintain structural stability, especially since the massive volume expansion of silicon-based materials during charging and discharging poses a severe challenge to the structural stability of the anode.
By increasing the fibrillation degree of the binder to 95% or more, and combining ultra-high molecular weight binders with a three-stage fibrillation, rapid cooling, and intermittent shearing process, a stable fiber network structure is formed, which alleviates the volume expansion of the negative electrode active material and optimizes the ratio between the negative electrode active material and the binder.
It effectively alleviates the volume expansion of the anode material, improves the cycle stability and lithium-ion transport efficiency of the battery, increases the energy density and dynamic performance of the battery, and enhances the toughness and production efficiency of the dry anode.
Smart Images

Figure CN120497283B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of batteries, in particular to a dry-method negative electrode, a preparation method thereof and a battery. BACKGROUND
[0002] The negative electrode sheet is a core component of a lithium ion battery, and the preparation of the negative electrode sheet is one of the key links affecting the performance of the battery. The traditional wet process needs to disperse the negative electrode material in an organic solvent to form a slurry, which is then coated on a current collector, and then subjected to drying, rolling and other processes to form a negative electrode sheet. Although this process is mature, it has problems such as high solvent cost, high energy consumption, easy cracking or binder migration during drying, and solvent residue that may affect the stability of the battery interface.
[0003] The dry-method process directly compresses the negative electrode powder to form a dry-method negative electrode, which has the advantages of process simplification, high interface stability and environmental friendliness compared to the wet process. In addition, in order to meet the urgent demand for higher energy density of lithium ion batteries, the negative electrode material is gradually changing from traditional graphite (theoretical specific capacity of about 372 mAh / g) to high specific capacity silicon-based materials (theoretical specific capacity of up to 4200 mAh / g). However, the volume expansion of silicon-based materials during battery charging and discharging can be as high as more than 300%, which poses a severe challenge to the stability of the negative electrode structure.
[0004] Therefore, how to improve the energy density of the battery while maintaining the stability of the dry-method negative electrode structure is a technical problem that needs to be solved urgently. SUMMARY
[0005] In view of the problems existing in the prior art, the present application provides a dry-method negative electrode, a preparation method thereof and a battery, which improve the problem that the energy density and the stability of the negative electrode are difficult to balance.
[0006] To achieve the above and other related objects, the first aspect of the present application provides a dry-method negative electrode, comprising a negative electrode current collector and a negative electrode film, the negative electrode film being arranged on at least one side of the negative electrode current collector; wherein the negative electrode film comprises a negative electrode active material and a binder, the negative electrode active material comprises a graphite-based material and / or a silicon material, and the degree of fibrillation of the binder in the negative electrode film is greater than or equal to 95%.
[0007] In an embodiment of the present application, the silicon content in the negative electrode active material is 0-50wt%.
[0008] In an embodiment of the present application, the silicon content in the negative electrode active material is X1wt%, the degree of fibrillation of the binder in the negative electrode film is X2%, and the dry-method negative electrode satisfies the following relationship: -99≤0.06X1-X2≤-95.
[0009] In an embodiment of the present application, the molecular weight of the binder is greater than or equal to 9000, and the melt viscosity of the binder at 380℃ is greater than or equal to 5.0 x 10 13 Pa·s.
[0010] In an embodiment of the present application, the content of the binder in the negative electrode film is 1wt% to 2wt%.
[0011] In an embodiment of the present application, the binder comprises one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, ethylene-octene copolymer, and polyimide.
[0012] In an embodiment of the present application, the negative electrode film further comprises a solid-state electrolyte and / or a conductive agent; the solid-state electrolyte comprises at least one of oxide solid-state electrolyte, sulfide solid-state electrolyte, and halide solid-state electrolyte; and the conductive agent comprises at least one of graphite, graphene, carbon black, carbon fiber, and carbon nanotube.
[0013] The second aspect of the present application provides a preparation method of a dry-method negative electrode, comprising the following steps:
[0014] mixing the negative electrode active material and the binder to obtain a mixture;
[0015] fibrillating the mixture to obtain a fibrillated material;
[0016] crushing and granulating the fibrillated material to obtain a negative electrode powder;
[0017] rolling the negative electrode powder into a film and thinning the film to a target surface capacity to obtain a negative electrode film;
[0018] compositing the negative electrode film with a negative electrode current collector to obtain a dry-method negative electrode.
[0019] In an embodiment of the present application, before mixing the negative electrode active material and the binder, the method further comprises: pre-mixing the negative electrode active material, a solid-state electrolyte, and a conductive agent, wherein, in the pre-mixing step, the linear speed of the stirring paddle is 20 to 40 m / s, the stirring time is 20 to 60 min, and the processing temperature is 5 to 60℃.
[0020] In an embodiment of the present application, in the step of mixing the negative electrode active material and the binder, the linear speed of the stirring paddle is 5 to 20 m / s, the stirring time is 20 to 60 min, and the processing temperature is 5 to 20℃.
[0021] In an embodiment of the present application, the step of fibrillating comprises:
[0022] The first stage fibrillation treatment: the treatment temperature is 20-40℃, the linear speed of the stirring paddle is 20-30m / s, and the stirring time is 10-30min;
[0023] The second stage fibrillation treatment: the treatment temperature is 60-80℃, the linear speed of the stirring paddle is 40-60m / s, and the stirring time is 10-30min;
[0024] The third stage fibrillation treatment: the treatment temperature is 90-120℃, the linear speed of the stirring paddle is 60-70m / s, and the stirring time is 60-120min;
[0025] Pulse cooling: the material after the third stage fibrillation treatment is cooled to 25-40℃ at a cooling rate of 10-15℃ / min, and intermittent low-speed shearing is applied, wherein the linear speed of the intermittent low-speed shearing is 3-10m / s.
[0026] In an embodiment of the present application, each pulse cycle in the pulse cooling step includes 5s of high-speed shearing at 8-10m / s and 10s of low-speed shearing at 3-5m / s.
[0027] The third aspect of the present application provides a battery, which comprises the dry-method negative electrode described in any of the above or prepared by any of the above preparation methods.
[0028] In summary, the dry-method negative electrode of the present application improves the fibrillation degree of the binder to 95% or above, reduces the proportion of binder particles that fail to fibrillate in the dry-method negative electrode, thereby improving the toughness and cohesion of the dry-method negative electrode, and effectively alleviates the volume expansion of the negative active material during charging and discharging; at the same time, the improvement of the fibrillation degree of the binder also reduces the barrier of residual granular binder to lithium ion transport, thereby improving the rate performance of the battery.
[0029] In addition, the improvement of the fibrillation degree of the binder in the dry-method negative electrode can reduce the content of the binder in the dry-method negative electrode, and the reduction of the content of the insulating binder can increase the transport channels of lithium ions, thereby improving the energy density and kinetic performance of the battery.
[0030] The ultra-high molecular weight binder can improve the fibrillation degree of the binder, and compared with the low molecular weight binder, the ultra-high molecular weight binder has a shorter time to reach saturation in fibrillation degree and a higher fibrillation degree, thereby greatly improving the production efficiency of the dry-method negative electrode.
[0031] The present application adopts an ultrahigh molecular weight binder, and the fibrillation degree of the binder in the dry negative electrode can be increased to more than 95% by combining a three-stage fibrillation process, rapid cooling and intermittent shearing, so as to improve the toughness and cohesion of the dry negative electrode, reduce the binder content in the dry negative electrode, and improve the energy density, rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description only constitute some embodiments of the present application, and for those skilled in the art, other embodiments can also be obtained from these drawings without creative labor.
[0033] Figure 1 Structure schematic diagram of the negative electrode sheet in an embodiment of the present application;
[0034] Figure 2 Flow chart of the preparation method of the negative electrode sheet in an embodiment of the present application.
[0035] Element number explanation:
[0036] 100, dry negative electrode; 110, negative electrode current collector; 120, negative electrode film. DETAILED DESCRIPTION
[0037] The embodiments of the present application will be described below through specific and concrete examples, and those skilled in the art can easily understand other advantages and effects of the present application from the content disclosed in the present description. The present application can also be implemented or applied through other different specific embodiments, and each detail in the present description can be modified or changed based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. The test methods in the following embodiments not marked with specific conditions are usually carried out according to the conventional conditions or the conditions suggested by each manufacturer.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application belongs. The terminology used in the present description is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application.
[0039] Unless otherwise defined or contradictory, the terms or phrases used herein have the following meanings:
[0040] The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0041] As used herein, the singular forms "a", "an" and "the" include plural referents unless the context clearly dictates otherwise. For example, "a" or "an" means one or more.
[0042] As used herein, "preferably," "more preferably," "even more preferably," and the like are used to mean that a described preference, feature, or characteristic is desired, but not necessarily required, and that other features, configurations, or characteristics can be useful in some embodiments. As used herein, "preferred" or "exemplary" or "better" or "more optimal" or the like, merely indicates that a described embodiment can be preferred or better or more optimal over other embodiments, but does not require a particular feature or characteristic. That is, use of the term "preferred" or "exemplary" or "better" or "more optimal" or the like does not require that a described embodiment is the only embodiment that can achieve a particular result or effect. Thus, the use of these terms is not intended to limit the scope of any claim.
[0043] As used herein, "further," "more," "furthermore," and the like are used to indicate that a described feature, characteristic, or effect is in addition to, or not mutually exclusive with, another described feature, characteristic, or effect. Thus, these terms do not preclude a feature, characteristic, or effect from being used in combination with other features, characteristics, or effects.
[0044] As used herein, a range of values, unless otherwise indicated, is intended to encompass both the range of values and individual values within the range of values. For example, a range of "1 to 10" is intended to encompass individual values of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, as well as ranges of 1-10, 2-9, 3-8, 4-7, 5-6, and 6-10. Likewise, a range of "1 to 10" is intended to encompass individual values of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, as well as ranges of 1-10, 2-9, 3-8, 4-7, 5-6, and 6-10. When multiple ranges of values are provided, the ranges can be combined.
[0045] A dry cathode is a cathode prepared by a dry process, in which the cathode active material, binder and other components are directly compressed into a self-supporting dry cathode. Therefore, the binder is crucial in the dry cathode.
[0046] At present, in order to improve the energy density of the battery, silicon-based materials are usually added to the dry cathode. However, the volume expansion of the silicon-based materials during the charging and discharging process of the battery is relatively large, and such a large volume expansion will affect the cycle performance of the battery. Increasing the content of the binder in the dry cathode can improve the toughness and cohesion of the dry cathode to a certain extent, and can resist the volume expansion of the cathode, but at the same time, it will hinder the ion transmission, thereby affecting the kinetic performance of the battery. The inventors have found in research that the binder in the dry cathode will form an elongated and interconnected fiber network during fibrillation. Such a fiber network has elasticity and can withstand the stress generated by the expansion of the cathode material to a certain extent. Once the stress generated by the expansion of the cathode material during the charging and discharging process exceeds the elastic limit of the fiber network, irreversible damage will occur to the fiber network, thereby affecting the cycle performance of the battery. Conversely, if the elastic limit of the fiber network structure formed by the fibrillation of the binder is greater than the stress generated by the volume expansion of the cathode material, the cycle stability can be maintained.
[0047] Based on this, the application provides a dry negative electrode, a preparation method of the dry negative electrode, and a battery comprising the dry negative electrode. By increasing the fibrillation degree of the binder in the dry negative electrode to 96% or above, the volume expansion of the negative electrode material can be effectively alleviated, and the cycle stability of the battery can be improved.
[0048] Please refer to Figure 1 The application provides a dry negative electrode, a preparation method of the dry negative electrode, and a battery comprising the dry negative electrode. By increasing the fibrillation degree of the binder in the dry negative electrode to 96% or above, the volume expansion of the negative electrode material can be effectively alleviated, and the cycle stability of the battery can be improved. Figure 1 Only the case of single-sided arrangement is shown, and the negative electrode current collector 110 has a first surface and a second surface arranged oppositely along the thickness direction of the negative electrode current collector 110, and the negative electrode film 120 can be arranged on one of the first surface and the second surface, or arranged on both the first surface and the second surface.
[0049] The negative electrode film 120 comprises a negative electrode active material and a binder, wherein the negative electrode active material, as the core material of the negative electrode film 120, can be selected according to actual application requirements. After the binder is fibrillated, a fiber network connected to each other and penetrating through the entire electrode is formed, and the negative electrode active material particles are fixed in the fiber network to form a complete negative electrode film 120 with certain mechanical strength and stability, and the negative electrode film 120 can be closely attached to the surface of the negative electrode current collector 110 to achieve good electrical contact. In addition, the fiber network builds a “bridge” between the particles to prevent excessive close accumulation of the particles during the calendering process, thereby creating and maintaining a large number of micron / sub-micron level pore channels connected to each other, and providing a guarantee for the transmission of lithium ions.
[0050] In some embodiments, the negative active material comprises a graphite-based material and / or a silicon material, wherein the graphite-based material can be natural graphite, artificial graphite, or a composite of natural graphite and artificial graphite, the natural graphite including but not limited to blocky graphite, flaky graphite, earthy graphite, and the artificial graphite including but not limited to single-crystal graphite, polycrystal graphite, pyrolytic graphite, and graphite fiber. The silicon material includes but is not limited to one or more of crystalline silicon, amorphous silicon, and organosilicon. That is, the negative active material can be a single graphite-based material, such as flaky graphite, or pyrolytic graphite, or graphite fiber, etc.; the negative active material can also be a single silicon material, such as crystalline silicon, or amorphous silicon, etc.; the negative active material can also be a combination of a graphite-based material and a silicon material, such as a combination of blocky graphite and single-crystal graphite, or a combination of single-crystal graphite and crystalline silicon, or a combination of flaky graphite, graphite fiber, and crystalline silicon, etc. However, the type of negative active material is not limited to the above-mentioned materials. Further, the negative active material is a combination of a graphite-based material and a silicon material, the graphite-based material has the advantages of high stability, long life, high initial efficiency, low cost, maturity, and reliability, but the specific capacity is relatively low, while the silicon material has an ultra-high theoretical specific capacity, and the combination of the graphite-based material and the silicon material can take advantage of both and greatly improve the energy density of the battery. However, the volume expansion of the silicon material during the charging and discharging process of the battery is extremely large, and the higher the silicon content in the negative active material, the greater the volume expansion of the negative electrode.
[0051] The inventors have found in their research that the fiber network formed by the fibrillation of the binder can absorb expansion energy through fiber sliding to relieve the volume expansion of the negative active material. Moreover, the higher the degree of fibrillation of the binder, the better the toughness of the fiber network structure formed, and the higher the expansion energy absorbed. Therefore, in the dry negative electrode of the present application, the degree of fibrillation of the binder is greater than or equal to 95%, and exemplarily can be 95%, 96%, 97%, 98%, or 99%, etc. At this time, the fiber network structure formed by the fibrillation of the binder can effectively relieve the volume expansion of the negative active material during the charging and discharging process of the battery, and improve the cycle stability of the battery. In addition, when the degree of fibrillation of the binder reaches 95% or above, the fiber network structure formed is more uniform, the pore channels supported by it are relatively straighter and more through, the degree of ion detouring is reduced, thereby significantly reducing the tortuosity of the pores, enabling the lithium ions to be transmitted more directly and quickly, thereby improving the transmission efficiency of the lithium ions and the rate performance of the battery.
[0052] In an embodiment, the silicon content in the negative active material is 0-50 wt%, illustratively, the silicon content in the negative active material can be 0 (i.e. pure graphite), 10 wt%, 30 wt% or 50 wt%. When the silicon content is less than 50 wt%, the fibrillation degree of the binder is increased to more than 95%, which can alleviate the volume expansion of the negative active material and maintain good cycle performance. When the silicon content in the negative active material is more than 50 wt%, the fibrillation degree of the binder is increased to more than 95%, which can alleviate the volume expansion of the negative active material to some extent, but the cycle performance of the battery is still poor, because the volume expansion of the negative active material is too large, and the increase in the fibrillation degree of the binder cannot completely solve the problem of volume expansion of the negative active material.
[0053] In order to better balance the relationship between the energy density and the cycle stability of the battery, the inventors have conducted a large number of studies on the silicon content in the negative active material and the fibrillation degree of the binder, and have obtained the following relationship: -99≤0.06X1-X2≤-95, wherein X1 represents the silicon content in the negative active material as X1 wt%, and X2 represents the fibrillation degree of the binder in the dry negative electrode as X2%. When the silicon content in the negative active material and the fibrillation degree of the binder satisfy the above relationship, the energy density can be improved while maintaining good cycle stability. In addition, from the above relationship, it can be seen that when the silicon content is less than 50 wt%, the increase in the fibrillation degree of the binder can maintain good cycle performance; and when the silicon content reaches 50 wt%, the fibrillation degree of the binder needs to be increased to more than 98% to maintain good cycle performance, at which time the ultra-high fiber density forms a three-dimensional interlocking structure to absorb the silicon expansion energy through fiber slip. If the fibrillation degree of the binder is less than 98%, good cycle performance cannot be maintained, because under high silicon content, the volume expansion of the silicon phase exceeds the elastic limit of the binder fiber network, resulting in irreversible cracking.
[0054] In an embodiment, the molecular weight of the binder is greater than or equal to 9000 kg / mol, and further, the molecular weight of the binder is 9000-15000 kg / mol, for example, it can be 9000 kg / mol, 11000 kg / mol, 13000 kg / mol, 15000 kg / mol, etc. The ultra-high molecular weight binder is composed of long molecular chains, which penetrate each other to form a topological entanglement network. When subjected to shear force, the topological entanglement network efficiently converts the mechanical shear force into continuous stretching orientation of the molecular chains, and forms a stable fiber structure under the protection of high melt strength and strain hardening. The molecular chains of the low molecular weight binder are short and there is no significant entanglement between the chains. When subjected to shear force, the whole chain slips or brittle fractures, and there is no obvious stretching. Therefore, the ultra-high molecular weight binder can maximize the fibrillation degree of the binder and greatly improve the toughness of the dry negative electrode.
[0055] In some embodiments, the binder has a melt viscosity at 380 °C greater than or equal to 5.0 x 10 13 Pa-s, further, can be 5.0 x 10 13 ~1 x 10 15 Pa-s, for example, can be 5 x 10 13 Pa-s, 1 x 10 14 Pa-s, 5 x 10 14 Pa-s, or 1 x 10 15 Pa-s, etc. The ultra-high melt viscosity means that the binder has better viscosity, which can make the dry cathode form a stable fiber network structure during the rolling process. Such a fiberized network can more effectively fix the active material of the cathode, and improve the mechanical strength and structural stability of the electrode.
[0056] In some embodiments, the binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-vinyl acetate copolymer (EVA), polypropylene (PP), polyethylene (PE), ethylene-octene copolymer (POE), polyimide (PI). That is, the binder can be a single material, such as polytetrafluoroethylene, or ethylene-tetrafluoroethylene copolymer, etc.; the binder can also be a combination of two or more materials, such as a combination of polytetrafluoroethylene and polypropylene, a combination of polytetrafluoroethylene, ethylene-octene copolymer and polyimide, etc.
[0057] The improved fibrillation of the binder can greatly improve the toughness and cohesion of the dry cathode, thereby reducing the content of the binder. Since the binder is insulating, the reduction of the binder content can increase the transmission channels of lithium ions, thereby improving the energy density and kinetic performance of the battery. In an embodiment, the content of the binder in the cathode film 120 is 1 wt% to 2 wt%, for example, can be 1 wt%, 1.5 wt%, 2 wt%, etc. Further, the use of a high molecular weight binder is more likely to improve its fibrillation in the dry cathode, thereby improving the toughness of the dry cathode. Therefore, the use of a high molecular weight binder can maintain a stable electrode structure while reducing the content of the binder.
[0058] In some embodiments, the negative electrode film 120 further comprises a conductive agent, which has good conductivity itself. The addition of the conductive agent in the dry negative electrode can effectively improve the conductivity of the electrode, reduce the resistance of the electrode, and thus improve the rate performance and the charging and discharging rate of the battery. The mass ratio of the conductive agent to the negative electrode film is (1-5):100, for example, 1:100, or 3:100, or 5:100, and the like. Illustratively, the conductive agent includes, but is not limited to, at least one of graphite, graphene, carbon black (Super p), carbon fiber (VGCF), and carbon nanotube, for example, graphite, or carbon black, or a combination of carbon black and carbon fiber, and the like. Further, the conductive agent is a combination of carbon black and carbon fiber, and the mass ratio of carbon black to carbon fiber is 1:(0.2-1.5), for example, 1:0.2, or 1:0.8, or 1:1.2, or 1:1.5, and the like. Further, the mass ratio of carbon black to carbon fiber is 1:1.
[0059] In some embodiments, the negative electrode film 120 further comprises a solid-state electrolyte, which can provide a path for lithium ion migration, so that lithium ions can shuttle back and forth between the negative electrode and the negative electrode, thereby realizing the charging and discharging process of the battery. In addition, the solid-state electrolyte can be closely combined with the negative electrode active material, reducing the occurrence of side reactions at the interface, reducing the interface resistance, and thus improving the overall performance and cycle life of the battery. As an example, the solid-state electrolyte includes at least one of oxide solid-state electrolyte, sulfide solid-state electrolyte, and halide solid-state electrolyte, for example, oxide solid-state electrolyte, or sulfide solid-state electrolyte, or a combination of oxide solid-state electrolyte and halide solid-state electrolyte, and the like.
[0060] The dry negative electrode of the present application can be used in a full solid-state battery (which can be referred to as a full solid-state dry negative electrode), or in a liquid battery or a semi-solid battery, which is not limited herein.
[0061] Please refer to Figure 2 The second aspect of the present application provides a preparation method of the above dry negative electrode, which comprises the following steps:
[0062] S1, mixing the negative electrode active material and the binder to obtain a mixture;
[0063] S2, performing fibrillation treatment on the mixture to obtain a fibrillated material;
[0064] S3, performing crushing and granulation treatment on the fibrillated material to obtain a negative electrode powder;
[0065] S4, rolling the negative electrode powder into a film and thinning to a target surface capacity to obtain a negative electrode film;
[0066] S5, compounding the negative electrode film with a negative electrode current collector to obtain a dry negative electrode.
[0067] Specifically, in step S1, if the raw material components of the negative electrode further include a solid-state electrolyte and / or a conductive agent, the negative electrode active material is pre-mixed with the solid-state electrolyte and / or the conductive agent before the negative electrode active material and the binder are mixed, to obtain a pre-mixed material with uniform mixing. In an embodiment, in the pre-mixing step, the linear speed of the stirring paddle is 20-40 m / s, the stirring time is 20-60 min, and the processing temperature is 5-60°C. For example, the linear speed of the stirring paddle can be 20 m / s, 30 m / s, or 40 m / s, etc., the stirring time can be 20 min, 40 min, or 60 min, etc., and the processing temperature can be low temperature 5°C or normal temperature 25°C, or high temperature 60°C, etc. The temperature in this step has little effect on the pre-mixing effect, and is not limited here. The parameters in the pre-mixing step can be set according to the actual processing conditions, as long as the negative electrode active material, the conductive agent, and the solid-state electrolyte are fully mixed and uniform. The reason for pre-mixing the negative electrode active material, the conductive agent, and the solid-state electrolyte is that during the mixing process, the collision and friction between the materials will generate heat, the longer the mixing time, the more heat generated, and the higher the temperature inside the material. If the binder is mixed with other materials, it may cause some of the binder to fibrillate in advance, affecting the uniformity of the binder dispersion.
[0068] After the pre-mixing is completed, the pre-mixed material is mixed with the binder to obtain a mixed material. In the mixing step, the linear speed of the stirring paddle is 5-20 m / s, the stirring time is 20-60 min, and the processing temperature is 5-20°C. For example, the linear speed of the stirring paddle can be 5 m / s, 10 m / s, 15 m / s, or 20 m / s, etc., the stirring time can be 20 min, 40 min, or 60 min, etc., and the processing temperature can be 5°C, 10°C, 15°C, or 20°C, etc. During the mixing of the binder, the linear speed and the processing temperature cannot be too high. If the linear speed is too high, it may cause the binder to agglomerate and break, and if the processing temperature is too high, it may cause some of the binder to fibrillate in advance, resulting in uneven dispersion of the binder. In some embodiments, the mass ratio of the negative electrode active material, the solid-state electrolyte, the conductive agent, and the binder in the mixed material is (60-70):(25-35):(1-5):(1-2), and the proportions of the substances can be adjusted within the above ranges.
[0069] Step S2 is to perform fibrillation treatment on the mixture to fully fibrillate the binder to form a fiber network structure, and fix the negative active material, the conductive agent, and the solid-state electrolyte in the fiber network structure. In an embodiment, the step adopts a three-stage fibrillation treatment, including: a first-stage fibrillation treatment, a second-stage fibrillation treatment, a third-stage fibrillation treatment, and pulse cooling. In the first-stage fibrillation treatment, the treatment temperature is 20-40°C, the linear speed of the stirring paddle is 20-30 m / s, and the stirring time is 10-30 min. Exemplarily, the treatment temperature of the first stage can be 20°C, 30°C, or 40°C, etc., the linear speed can be 20 m / s, 25 m / s, or 30 m / s, etc., and the stirring time can be 10 min, 20 min, or 30 min, etc. In the second-stage fibrillation treatment, the treatment temperature is 60-80°C, the linear speed of the stirring paddle is 40-60 m / s, and the stirring time is 10-30 min. Exemplarily, the treatment temperature of the second stage can be 60°C, 70°C, or 80°C, etc., the linear speed can be 40 m / s, 50 m / s, or 60 m / s, etc., and the stirring time can be 10 min, 20 min, or 30 min, etc. In the third-stage fibrillation treatment, the treatment temperature is 90-120°C, the linear speed of the stirring paddle is 60-70 m / s, and the stirring time is 60-120 min. Exemplarily, the treatment temperature of the third stage can be 90°C, 100°C, 110°C, or 120°C, etc., the linear speed can be 60 m / s, 65 m / s, or 70 m / s, etc., and the stirring time can be 60 min, 80 min, 100 min, or 120 min, etc. In the pulse cooling step, the cooling rate is 10-15°C / min, and the target cooling temperature is 25-40°C. Exemplarily, the cooling rate of the pulse cooling can be 10°C / min, 12°C / min, or 15°C / min, etc., and the target cooling temperature can be 25°C, 30°C, 35°C, or 40°C, etc. One pulse cycle of the intermittent low-speed shearing includes high-speed shearing at 8-10 m / s for 5 s and low-speed shearing at 3-5 m / s for 10 s. Exemplarily, the linear speed of the high-speed shearing can be 8 m / s, 9 m / s, or 10 m / s, etc., and the linear speed of the low-speed shearing can be 3 m / s, 4 m / s, or 5 m / s, etc. In the three-stage fibrillation step, the fibrillation degree of the binder is maximized through the synergistic effect of the stepwise temperature rise and the segmented speed-up shearing, while the binder is prevented from excessive breakage or agglomeration. Then, the fiberized structure is locked through the rapid cooling and the intermittent shearing to prevent the fibers from shrinking due to natural cooling.
[0070] Step S3 is to crush and granulate the fibrillated material to obtain the negative electrode powder meeting the processing requirements. After high-strength shearing, the binder forms an intertwined fiber network, which wraps the negative active material, the conductive agent, and the solid-state electrolyte to form a fiber clump. The particle size of the fiber clump is large, and the flowability is poor, so the fiber clump cannot be uniformly spread on the negative electrode current collector. The fibrillation and crushing treatment can disperse the fiber clump into microparticles, realize uniform mixing of the components, and granulation can spheroidize the irregular particles. The spherical particles plastically deform to form a dense electrode sheet when subjected to pressure. The crushing and granulation treatment can use a mechanical pulverizer and a granulator. The particle size after crushing and granulation can be selected according to actual requirements, which is not limited here.
[0071] Step S4 is to form a film by multi-roll continuous rolling of the negative electrode powder and to thin the film to a target surface capacity to obtain a negative electrode film. The target surface capacity refers to the amount of charge (capacity) designed or expected to be stored on the electrode per unit area, and is expressed in mAh / cm². The target surface capacity can be set according to actual requirements, which is not limited here.
[0072] Step S5 is to obtain a dry-type negative electrode by hot-pressing the negative electrode film obtained in step S4 and the negative electrode current collector.
[0073] The three-stage fibrillation, rapid cooling, and intermittent shearing process adopted by the present application can maximize the highest fibrillation degree that the binder can achieve, and form a stable fiber network structure. Further, the use of an ultrahigh molecular weight binder can achieve a shorter saturation time than a low molecular weight binder, which greatly improves the production efficiency of the dry-type negative electrode.
[0074] The third aspect of the present application provides a battery comprising the dry-type negative electrode described above. The battery can be a full-solid-state battery, a semi-solid-state battery, or a liquid battery.
[0075] In an embodiment, the battery is a full-solid-state battery, which further comprises a positive electrode sheet, a solid-state electrolyte layer, and other necessary components. The solid-state electrolyte layer is arranged between the dry-type negative electrode and the negative electrode sheet, and is used to provide a channel for ion transmission between the positive and negative electrodes, while preventing the transmission of electrons, thereby avoiding the short circuit phenomenon. The full-solid-state battery can provide users with a safer next-generation power battery by replacing the flammable liquid electrolyte with a solid-state electrolyte, and has higher energy density and better long-term cycle performance.
[0076] In some embodiments, the positive electrode tab includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode current collector is, for example, an aluminum foil or a carbon-coated aluminum foil, etc., and the positive electrode active material layer can be disposed on one side surface of the positive electrode current collector or on both side surfaces. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material includes, but is not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based oxide, which can be a single material, such as lithium cobalt oxide, or lithium nickel cobalt manganese oxide, or lithium nickel manganese oxide, etc.; or a combination of multiple materials, such as a combination of lithium cobalt oxide and lithium nickel oxide, a combination of lithium nickel cobalt aluminum oxide, lithium-rich-based oxide, and lithium nickel cobalt manganese oxide, etc. The conductive agent includes, but is not limited to, one or more of graphite, graphene, carbon black, carbon fiber, and carbon nanotube, such as graphite, or a combination of carbon black and carbon fiber, etc. The binder varies depending on the preparation process of the positive electrode tab, and when the positive electrode tab is prepared by a wet process, the binder is selected from any one or more of polyvinylidene fluoride, polyethylene oxide, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, ethylene-propylene-diene terpolymer, and polyhexafluoropropylene. When the positive electrode tab is prepared by a dry process, the binder is selected from one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, ethylene-octene copolymer, and polyimide.
[0077] The solid-state electrolyte layer includes a solid-state electrolyte, which includes, but is not limited to, an oxide solid-state electrolyte, a sulfide solid-state electrolyte, a halide solid-state electrolyte, and a polymer solid-state electrolyte, which can be a single material or a combination of multiple materials. The solid-state electrolyte layer is prepared by a wet process or a dry process. The specific process is not described in detail here.
[0078] Full solid-state battery assembly: The prepared dry negative and positive electrode tabs are placed on both sides of the solid-state electrolyte layer for assembly, and a full solid-state battery is obtained.
[0079] It should be noted that the structures not described in detail in the above battery can be set according to conventional techniques in the art, and will not be described here.
[0080] The battery of this invention can be used in the form of a single cell, a battery module, or a battery pack to power electronic devices. Electronic devices include, but are not limited to, mobile phones, tablets, laptops, electric toys, electric vehicles, new energy vehicles, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc.
[0081] The technical solution of the present invention will be described in detail below through several specific embodiments and comparative examples. Unless otherwise stated, the raw materials and reagents used in the following embodiments are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the embodiments are all commercially available.
[0082] Example 1
[0083] The first aspect of this embodiment provides a dry negative electrode, which includes a negative current collector and a negative electrode membrane disposed on the negative current collector. The negative current collector is a carbon-coated copper foil, and the negative electrode membrane includes a negative active material (silicon-carbon material), a solid electrolyte (Li6PS5Cl), a conductive agent (super p and VGCF), and a binder (PTFE).
[0084] The aforementioned silicon-carbon material is sourced from Guangdong Zhuguang New Energy Technology Co., Ltd., model number 650, with a silicon content of 13%; Li6PS5Cl is sourced from Shandong Xinjie Energy Lithium Battery Co., Ltd., model number LPSCl; the conductive agents are Super P (Tianjin Youmeng Chemical Technology Co., Ltd., Super P) and VGCF (Showa Denko Co., Ltd., VGCF-H) in a 1:1 mass ratio; PTFE is sourced from 3M, model number Dyneon™ TF-1620, with a molecular weight of 10000 kg / mol. The melt viscosity (380℃) of the ultra-high molecular weight binder is 1×10⁻⁶. 14 Pa·s.
[0085] In the dry anode, the mass ratio of silicon-carbon material, Li6PS5Cl, conductive agent and PTFE is 70:25:3:2.
[0086] The second aspect of this embodiment provides a method for preparing the above-mentioned dry negative electrode, characterized by comprising the following steps:
[0087] (1) Premixing: Silicon carbide, Li6PS5Cl, Super p, and VGCF are mixed evenly to obtain a premix. The linear velocity of the stirring paddle in the premixing step is 30 m / s, the stirring time is 30 min, and the processing temperature is 25 ℃.
[0088] (2) Mixing: mixing the premix and the binder PTFE to obtain a mixture, the linear speed of the stirring paddle in the mixing step is 15 m / s, the stirring time is 30 min, and the processing temperature is 10 ℃;
[0089] (3) fibrillation: fibrillating the mixture to obtain a fibrillated material, the first stage processing temperature is 25 ℃, the linear speed of the stirring paddle is 20 m / s, and the stirring time is 10 min; the second stage processing temperature is 80 ℃, the linear speed of the stirring paddle is 50 m / s, and the stirring time is 10 min; the third stage processing temperature is 120 ℃, the linear speed of the stirring paddle is 70 m / s, and the stirring time is 90 min;
[0090] (4) pulse cooling: after the fibrillation is completed, the temperature is rapidly cooled to 25 ℃ at a rate of 15 ℃ / min, and intermittent low-speed shearing is applied, one pulse cycle is 10 m / s stirring for 5 s and 5 m / s stirring for 10 s;
[0091] (5) crushing and granulating: crushing and granulating the fibrillated material to obtain a negative electrode powder;
[0092] (6) multi-roll continuous rolling film forming: forming a negative electrode film by multi-roll continuous rolling of the negative electrode powder and thinning to a surface capacity of 4 mAh / cm 2 to obtain a negative electrode film;
[0093] (7) compounding: compounding the negative electrode film with a current collector coated carbon copper foil to obtain a dry-method negative electrode.
[0094] The third aspect of the embodiment provides a full-solid-state lithium ion battery, which comprises the above dry-method negative electrode, a counter electrode, and a solid-state electrolyte layer.
[0095] The solid-state electrolyte layer is composed of Li6PS5Cl, and the counter electrode is a lithium-indium alloy sheet (diameter φ=10 mm).
[0096] The preparation steps of the full-solid-state lithium ion battery are as follows:
[0097] Step one: 1000 mg of Li6PS5Cl powder is placed in a mold with a diameter of 10 mm, and is pressed to 100 MPa to obtain a solid-state electrolyte layer;
[0098] Step two: the dry-method negative electrode and the lithium-indium alloy sheet are sequentially placed on both sides of the solid-state electrolyte layer for assembly; after assembly, the pressure is increased to 100 MPa, and the nut at the top of the stand is tightened to constant pressure, thereby obtaining a full-solid-state lithium ion battery.
[0099] Note: The assembly process is completed in an argon atmosphere glove box, and the diameters of the above dry-method negative electrode and the lithium-indium alloy sheet are both 10 mm.
[0100] Example 2
[0101] The difference between this example and Example 1 is that the binder PTFE is sourced from Asahi, with the model number of Algoflon® F208, and the molecular weight is 13000 kg / mol. The melt viscosity of the binder (380°C) is 5 x 10 13 Pa·s. The silicon content in the silicon-carbon material is 26%, sourced from Guangdong Chucguang New Energy Technology Co., Ltd., with the model number of Silicon-carbon material 1200.
[0102] Example 3
[0103] The difference between this example and Example 1 is that the binder PTFE is sourced from Asahi, with the model number of Algoflon® F208, and the molecular weight is 13000 kg / mol. The melt viscosity of the binder (380°C) is 5 x 10 14 Pa·s. The silicon content in the silicon-carbon material is 26%, sourced from Guangdong Chucguang New Energy Technology Co., Ltd., with the model number of Silicon-carbon material 1200.
[0104] Example 4
[0105] The difference between this example and Example 1 is that the binder PTFE is sourced from Dongyuke Group, with the model number of DF-204A, and the molecular weight is 15000 kg / mol. The melt viscosity of the binder (380°C) is 1 x 10 15 Pa·s. The silicon content in the silicon-carbon material is 50%, sourced from Changzhou Siyuan New Energy Materials Co., Ltd., with the model number of NSC9100.
[0106] Example 5
[0107] The difference between this example and Example 4 is that the content of the binder is 1%, and the fibrillation degree of the binder is 99%.
[0108] Example 6
[0109] The difference between this example and Example 4 is that the binder PTFE is sourced from Asahi, with the model number of Algoflon® F208, and the molecular weight is 13000 kg / mol. The melt viscosity of the binder (380°C) is 5 x 10 14 Pa·s.
[0110] Example 7
[0111] The difference between this example and Example 1 is that the binder PTFE is sourced from Dongyuke Group, with the model number of DF-204A, and the molecular weight is 15000 kg / mol. The melt viscosity of the binder (380°C) is 1 x 10 15 Pa·s.
[0112] Example 8
[0113] The difference between this example and Example 1 is that the binder PTFE, which is derived from Kureha, is Fluon® G190, with a molecular weight of 9000 kg / mol, and the melt viscosity of the binder (380℃) is 5 x 10 13 Pa·s.
[0114] Example 9
[0115] The difference between this example and Example 1 is that the content of the binder is 1.5%, and the proportions of other components remain unchanged.
[0116] Example 10
[0117] The difference between this example and Example 1 is that the content of the binder is 1%, and the proportions of other components remain unchanged.
[0118] Example 11
[0119] The difference between this example and Example 4 is that the pulse cooling step in the preparation method: the third stage processing temperature in the fibrillation treatment step is 90℃, the linear speed of the stirring paddle is 60 m / s, and the stirring time is 120 min; the rest of the implementation process is the same.
[0120] Example 12
[0121] The difference between this example and Example 4 is that the pulse cooling step in the preparation method: after the fiberization is completed, it is quenched to 40℃ at a rate of 10℃ / min, while intermittent low-speed shearing is applied, one pulse cycle is 8 m / s stirring for 5 s and 3 m / s stirring for 10 s; the rest of the implementation process is the same.
[0122] Example 13
[0123] The difference between this example and Example 1 is that LNMO pole pieces are used instead of lithium-indium alloy.
[0124] The composition of the LNMO positive pole piece: the mass ratio of LNMO, Li6PS5Cl, conductive carbon black and binder (PTFE) is 85:13:1:1.
[0125] The LNMO is specifically single-crystal LiNi 0.5 Mn 1.5 O4 coated with Li2ZrO3; which is derived from Xiamen Tungsten Co., Ltd., and the model is XW46.
[0126] Example 14
[0127] This comparative example is the same as the implementation of Example 3, except that the content of the binder is 4%.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 2 is that there is no pulse cooling step in the preparation process.
[0130] Comparative Example 2
[0131] The difference between this comparative example and Example 4 is that the existing process is used for preparation, i.e. the fibrillation step is: the linear speed of the stirring paddle is 40 m / s, the stirring time is 30 min, the treatment temperature is 100°C, and there is no pulse cooling step.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 1 is that the PTFE is from Daikin, the model is Polyflon™ M-18, and the molecular weight is 6000 kg / mol. The melt viscosity of the binder (380°C) is 1 x 10 13 Pa·s.
[0134] Comparative Example 4
[0135] The difference between this comparative example and Example 9 is that the existing process is used for preparation, i.e. the fibrillation step is: the linear speed of the stirring paddle is 40 m / s, the stirring time is 30 min, the treatment temperature is 100°C, and there is no pulse cooling step.
[0136] Comparative Example 5
[0137] The difference between this comparative example and Example 4 is that the binder content is 10 wt%.
[0138] Comparative Example 6
[0139] The difference between this comparative example and Example 13 is that the molecular weight of the binder is 6000 kg / mol.
[0140] Table 1: Various parameters of Examples 1-14 and Comparative Examples 1-6
[0141]
[0142] To verify the performance of the dry method negative electrode of the present application, the inventors respectively tested the performance of the dry method negative electrode of Examples 1-14 and Comparative Examples 1-6 and the all-solid-state lithium ion battery comprising the dry method negative electrode, the testing method is as follows, and the testing results are shown in Table 2.
[0143] (1) X-ray diffraction (XRD) is used to observe the fibrillation degree of the binder in the dry cathode. For PTFE, a typical crystalline peak appears at 2Q ~ 18° (100 crystal plane). The value obtained by integrating this peak is the peak area. The ratio of the peak area of the dry cathode at 18° to the peak area of the original PTFE powder at 18° is taken as the fibrillation degree of the binder in the dry cathode.
[0144] (2) PTFE has a unique infrared absorption peak (such as the C-F bond vibration peak at 1200-1300 cm -1 -1), which can be quantitatively analyzed by FTIR. Operation steps: directly use ATR (attenuated total reflection) mode testing, collect the infrared spectrum of the dry cathode sample, and quantitatively analyze the content of PTFE by standard curve or peak area integration.
[0145] (3) The molecular weight of PTFE is tested by gel permeation chromatography. PTFE in the dry cathode is dissolved in hexafluoroisopropanol, and after filtration, PTFE-hexafluoroisopropanol solution is obtained. The PTFE-hexafluoroisopropanol solution is injected into the gel permeation chromatography system using a syringe. The mobile phase is hexafluoroisopropanol, and the flow rate is usually 0.5-1.0 mL / min. Run the chromatographic analysis, read the retention time of the PTFE sample from the chromatogram, and convert the retention time of the sample to molecular weight according to the calibration curve.
[0146] (4) The test standard of melt viscosity is ASTM D1238. PTFE powder is loaded into a high-temperature capillary rheometer, and the thermal history is eliminated at 380°C for 10 minutes. A standard load (usually 5 kg) is applied, and the flow rate of the melt through the fixed diameter capillary is measured. The apparent shear viscosity is calculated according to the Poiseuille equation. The test needs to be carried out under nitrogen protection to avoid thermal degradation.
[0147] (5) Cathode tensile strength test: the dry cathode is cut into a long strip sample with a width of 20 mm and a length of 100 mm. The tensile strength of the dry cathode is tested at a rate of 100±10 mm / min using a tensile testing machine.
[0148] (6) Battery performance test: after the full-solid-state lithium ion battery was constant volume, long cycle charging and discharging was carried out at 25°C, and the number of cycles at room temperature was measured; the test conditions were that after the battery was constant volume, long cycle charging and discharging test was carried out, the first constant volume discharge specific capacity and the number of cycles at room temperature when SOH (State of Health) was 80% were recorded; the working voltage range of the battery of examples 1-12, 14 and comparative examples 1-5 was -0.615V-1.4V. The constant volume current was 0.6mA. The discharge specific capacity measured under the condition of 2C rate was taken as the rate performance. For example 13 and comparative example 6, the working voltage range of the battery was 2V-4.85V, and the test method was the same as that of other examples and comparative examples.
[0149] Table 2: Performance of examples 1-14 and comparative examples 1-6
[0150]
[0151] As can be seen from table 1 and table 2, examples 1-4, keeping the binder content and preparation process of the dry cathode the same, the degree of fibrillation of the binder in the dry cathode is adjusted by adjusting the molecular weight of the binder, so that it increases with the increase of the silicon content in the cathode active material, thereby relieving the expansion of the cathode material during the charging and discharging process of the battery. The test results show that: with the increase of the silicon content in the cathode active material, the first cycle specific capacity of the battery increases, and because the degree of fibrillation of the binder in the dry cathode reaches more than 95%, the dry cathode has high toughness and can absorb the volume expansion energy during the charging and discharging process of the cathode, therefore, the cathode with high silicon content can still maintain good cycle stability. In addition, the higher the degree of fibrillation of the binder, the more uniform the fiber network structure formed by fibrillation, and the less the proportion of binder particles that have not been fibrillated, the lithium ion transmission is reduced, which can shorten the transmission path of lithium ions, thereby improving the rate performance of the battery. Therefore, the batteries of examples 1-4 have good cycle stability and also have good rate performance.
[0152] Examples 1 and comparative example 3, the silicon content in the cathode active material is 13%, the degree of fibrillation of the binder in example 1 is 96%, and the degree of fibrillation of the binder in comparative example 3 is less than 96%, the tensile strength of the cathode, the first cycle discharge specific capacity of the battery, the cycle stability and the rate performance of example 1 are obviously improved compared with comparative example 3.
[0153] The negative electrode active material of Example 2 and Comparative Example 1 is pure graphite, and the fibrillation degree of the binder in Example 2 reaches 95%, while the fibrillation degree of the binder in Comparative Example 1 does not reach 95% (94%). The test results show that the tensile strength of the negative electrode, the first circle discharge specific capacity of the battery, the cycle stability and the rate capability of Example 2 are all obviously improved. This shows that when the fibrillation degree of the binder reaches 95% or above, the fiber network structure formed can relieve the volume expansion of the negative electrode material, thereby improving the cycle performance of the battery. In addition, the higher the fibrillation degree of the binder, the higher the toughness and cohesion of the dry negative electrode, the less the obstruction of the ion transmission path, and the better the tensile strength and rate capability of the negative electrode.
[0154] Examples 4-6 and Comparative Example 2, the silicon content in the negative electrode active material is 50%. From the test results, it can be seen that when the fibrillation degree of the binder is increased to 98% or above, the battery has good cycle stability; if the fibrillation degree of the binder in the dry negative electrode reaches 95% but is lower than 98% (not in accordance with the relationship between the silicon content and the fibrillation degree), the cycle stability of the battery is slightly poor; if the fibrillation degree of the binder in the dry negative electrode is lower than 95%, the cycle stability of the battery is sharply decreased. This is because: under high silicon content, the volume expansion of the negative electrode during the charging and discharging process of the battery is relatively large. When the fibrillation degree of the binder reaches 98% or above, the ultra-high fiber density forms a three-dimensional interlocking structure, which absorbs the silicon expansion energy through fiber sliding (non-fracture). If the fibrillation degree of the binder is lower than 98% but higher than 95%, it can absorb a certain amount of silicon expansion energy, but not completely, so the cycle stability of the battery is slightly poor. If the fibrillation degree of the binder is lower than 95%, the volume expansion of the silicon phase exceeds the elastic limit of the binder fiber network, resulting in irreversible cracks. The process conditions of Example 4 and Example 5 are the same, but the content of the binder is different. The lower the content of the binder, the higher the fibrillation degree under the same process conditions, but the performance of the binder is slightly reduced due to the low content, so the comprehensive performance of Example 4 and Example 5 is not much different.
[0155] Examples 1, 7 and 8, the silicon content in the dry negative electrode remains the same, and the fibrillation degree of the binder is adjusted by adjusting the molecular weight of the binder. From the test results, it can be seen that the higher the fibrillation degree of the binder, the better the tensile strength of the negative electrode, the discharge specific capacity, the cycle stability and the rate capability of the battery. This is because the higher the fibrillation degree of the binder, the more uniform the fiber network structure formed, the higher the toughness and cohesion of the dry negative electrode, and the higher the transmission efficiency of lithium ions.
[0156] Example 1, 9-10, keeping the molecular weight of the binder and the process conditions unchanged, adjusting the content of the binder in the dry method negative electrode, under the same process conditions, the appropriate amount of binder can be fully fibrillated, and excessive binder cannot be fully fibrillated, thereby reducing the fibrillation degree of the binder, and the binder that cannot be fibrillated is distributed in the fiber network in the form of large particles, hindering the transmission of lithium ions, thereby affecting the rate performance of the battery. At the same time, the high content of the insulating binder will affect the energy density and dynamics of the battery. When the content of the binder is 1% to 2%, the comprehensive performance of the battery is better.
[0157] Comparative Example 4 and Example 10 both use a low content of binder, and Comparative Example 4 uses the existing process. By comparison, it can be seen that the preparation process of the present application can achieve a fibrillation degree of the binder of more than 95%, while the fibrillation degree of the existing process cannot reach 95%, and therefore the performance of the battery of Comparative Example 4 is poor.
[0158] Examples 4, 11 and 12, keeping the molecular weight and content of the binder unchanged, adjusting the fibrillation degree of the binder by adjusting the fibrillation process. The three-stage fibrillation process cooperates with the stepwise heating and segmented speed-up shearing to avoid excessive breakage or agglomeration of the binder, and at the same time, through the high linear speed and time of the third stage, the highest fibrillation degree that the binder can reach is maximized, and the fibrillation structure is locked through rapid cooling and intermittent shearing.
[0159] Example 4 and Comparative Example 5, keeping the molecular weight of the binder unchanged and the fibrillation process unchanged, increasing the content of the binder from 2wt% to 10wt%, the tensile strength of the negative electrode is improved, but the rate performance, capacity and cycle performance of the battery are poor. This shows that: using a high molecular weight binder and the best process conditions, if the content of the binder is too high, the fibrillation degree cannot be fully fibrillated, so the fibrillation degree of the binder will be reduced. Raising the fibrillation of the binder to more than 95% can reduce the amount of binder while improving the rate performance and cycle performance of the battery. This is because the high fibrillation degree of the binder makes the dry method negative electrode have high toughness, thereby maintaining stability while reducing the content of the binder.
[0160] Example 3 and Example 14, when the content of silicon in the negative electrode active material is less than 50% (26%), by reducing the molecular weight of the binder and increasing the content of the binder, although the cycle stability can be maintained, the capacity and rate performance of the battery are slightly worse than the higher fibrillation degree, because the binder itself is insulating, increasing the content of the binder can improve the cohesion of the negative electrode film, but at the same time it will hinder the transmission of ions, therefore, the capacity and rate performance of Example 14 with high binder content are slightly worse than Example 3 with low binder content.
[0161] In Example 13 and Comparative Example 6, the positive active material is LNMO, the degree of fibrillation of the binder of the dry negative electrode in Example 13 reaches 96%, and the degree of fibrillation of the binder of the dry negative electrode in Comparative Example 6 is only 90%. The test results show that the capacity, cycle performance and rate performance of the battery in Example 13 are better than those in Comparative Example 6, indicating that the mechanism of improving the capacity, rate performance and cycle performance of the battery by the degree of fibrillation of the binder reaching 95% or more is applicable to both full batteries and half batteries.
[0162] The dry negative electrode of the present application can reduce the proportion of binder particles that fail to fibrillate by improving the degree of fibrillation of the binder to more than 95%, greatly improving the toughness and cohesion of the dry negative electrode, thereby relieving the volume expansion of the negative material during charging and discharging and improving the cycle stability of the battery. At the same time, it can also reduce the barrier of granular binder to lithium ion transport and improve the rate performance of the battery. In addition, the degree of fibrillation of the binder is improved, and the high-toughness dry negative electrode can reduce the content of the binder therein. The reduction of the content of the insulating binder can increase the transport channels of lithium ions, thereby improving the energy density and kinetic performance of the battery. Therefore, the present application effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0163] The above examples only illustrate the principles and effects of the present application and are not intended to limit the present application. Any person skilled in the art can modify or change the above examples without departing from the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical idea disclosed by the present application should be covered by the claims of the present application.
Claims
1. A dry-process negative electrode, characterized in that, include: Negative electrode current collector; A negative electrode membrane is disposed on at least one side of the negative electrode current collector; The negative electrode film includes a negative electrode active material and a binder. The negative electrode active material includes graphite-based materials and / or silicon materials. The degree of fibrillation of the binder in the negative electrode film is greater than or equal to 95%. The degree of fibrillation of the binder in the dry negative electrode is analyzed by X-ray diffraction. The characteristic diffraction peaks of the binder are integrated, and the obtained value is the peak area. The ratio of the peak area of the characteristic diffraction peak of the binder in the dry negative electrode to the peak area of the initial binder powder in the corresponding characteristic diffraction peak is used as the degree of fibrillation of the binder in the dry negative electrode. The dry-process negative electrode is prepared by the following method: mixing negative electrode active material and binder to obtain a mixture; subjecting the mixture to fibrillation treatment to obtain fibrillated material; subjecting the fibrillated material to crushing and granulation treatment to obtain negative electrode powder; rolling the negative electrode powder into a film and thinning it to the target areal capacity to obtain a negative electrode film; and combining the negative electrode film with a negative electrode current collector to obtain a dry-process negative electrode. The fibrillation process includes: The first stage of fibrillation treatment: the treatment temperature is 20~40℃, the linear velocity of the stirring paddle is 20~30m / s, and the stirring time is 10~30min; The second stage of fibrillation treatment: the treatment temperature is 60~80℃, the linear velocity of the stirring paddle is 40~60m / s, and the stirring time is 10~30min; The third stage of fibrillation treatment: the treatment temperature is 90~120℃, the linear velocity of the stirring paddle is 60~70m / s, and the stirring time is 60~120min; Pulse cooling: The material after the third stage fibrillation treatment is cooled to 25-40°C at a cooling rate of 10-15°C / min, while intermittent low-speed shearing is applied, wherein the linear velocity of the intermittent low-speed shearing is 3-10 m / s.
2. The dry-process negative electrode according to claim 1, characterized in that, The silicon content in the negative electrode active material is 0~50wt%.
3. The dry-process negative electrode according to claim 2, characterized in that, The silicon content in the negative electrode active material is X1wt%, the degree of fibrillation of the binder in the negative electrode membrane is X2%, and the dry negative electrode satisfies the following relationship: -99≤0.06X1-X2≤-95.
4. The dry-process negative electrode according to claim 1, characterized in that, The adhesive has a molecular weight greater than or equal to 9000 kg / mol, and its melt viscosity at 380°C is greater than or equal to 5.0 × 10⁻⁶. 13 Pa·s.
5. The dry-process negative electrode according to claim 1, characterized in that, The binder content in the negative electrode film is 1wt%~2wt%.
6. The dry-process negative electrode according to claim 1, characterized in that, The adhesive includes one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, ethylene-octene copolymer, and polyimide.
7. The dry-process negative electrode according to claim 1, characterized in that, The negative electrode membrane also includes a solid electrolyte and / or a conductive agent; The solid electrolyte includes at least one of oxide solid electrolyte, sulfide solid electrolyte and halide solid electrolyte; The conductive agent includes at least one of graphite, graphene, carbon black, carbon fiber, and carbon nanotubes.
8. A method for preparing a dry negative electrode according to any one of claims 1-7, characterized in that, Includes the following steps: The negative electrode active material and the binder are mixed to obtain a mixture; The mixture is subjected to fibrillation treatment to obtain fibrillated material; The fibrillated material is crushed and granulated to obtain negative electrode powder; The negative electrode powder is rolled into a film and thinned to the target surface capacity to obtain a negative electrode film. The negative electrode membrane is combined with the negative electrode current collector to obtain a dry negative electrode. The fibrillation process includes: The first stage of fibrillation treatment: the treatment temperature is 20~40℃, the linear velocity of the stirring paddle is 20~30m / s, and the stirring time is 10~30min; The second stage of fibrillation treatment: the treatment temperature is 60~80℃, the linear velocity of the stirring paddle is 40~60m / s, and the stirring time is 10~30min; The third stage of fibrillation treatment: the treatment temperature is 90~120℃, the linear velocity of the stirring paddle is 60~70m / s, and the stirring time is 60~120min; Pulse cooling: The material after the third stage fibrillation treatment is cooled to 25-40°C at a cooling rate of 10-15°C / min, while intermittent low-speed shearing is applied, wherein the linear velocity of the intermittent low-speed shearing is 3-10 m / s.
9. The method for preparing a dry negative electrode according to claim 8, characterized in that, Before mixing the negative electrode active material and the binder, the process further includes: premixing the negative electrode active material, the solid electrolyte and the conductive agent. In the premixing step, the linear velocity of the stirring paddle is 20~40m / s, the stirring time is 20~60min, and the processing temperature is 5~60℃.
10. The method for preparing a dry negative electrode according to claim 8, characterized in that, In the step of mixing the negative electrode active material and the binder, the linear velocity of the stirring paddle is 5~20m / s, the stirring time is 20~60min, and the treatment temperature is 5~20℃.
11. The method for preparing a dry negative electrode according to claim 8, characterized in that, In the pulse cooling step, each pulse cycle includes a high-speed shearing of 8~10m / s for 5s and a low-speed shearing of 3~5m / s for 10s.
12. A battery, characterized in that, Includes the dry anode as described in any one of claims 1-7, or the dry anode prepared by the preparation method described in any one of claims 8-11.
Citation Information
Patent Citations
Binder for dry-method electrode and preparation method thereof
CN115863639A
Efficient fibrosis method of dry-method electrode binder and application of dry-method electrode binder in electrode slice
CN117790799A
Dry-method membrane preparation method based on binder fibrillation
CN118099344A
High-load dry-process composite positive pole piece and preparation method thereof
CN118841521A
Method for controlling fibrillation degree of negative pole piece prepared by dry method
CN120033210A